2020
DOI: 10.1177/1534735420942587
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Banxia XieXin Decoction, a Blended Traditional Chinese Medicine, as Monotherapy for Patients With Advanced Hepatocellular Carcinoma

Abstract: Purpose: To explore a new therapeutic option for patients with hepatocellular carcinoma (HCC), the efficacy and safety of a group of traditional Chinese medicines (Banxia XieXin recipe) as monotherapy for patients with advanced HCC was studied. Materials and Methods: The study included 68 patients with advanced HCC from August 16,2016 to August 15,2019 for analysis. These eligible patients received treatment with Banxia XieXin recipe for at least 1 month. The primary endpoints were progression-free survival (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Yan et al 5 showed that BXXX had a significant relieving effect on colon cancer in nude mice. Wang et al 15 evaluated the efficacy and safety of BXXX in advanced liver cancer treatment and found that BXXX could prolong the overall survival of liver cancer patients without obvious adverse reactions. So far, studies on the therapeutic potential of BXXX in GC have been insufficient as there is only one medical paper available on the literature database that is related to such subject.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al 5 showed that BXXX had a significant relieving effect on colon cancer in nude mice. Wang et al 15 evaluated the efficacy and safety of BXXX in advanced liver cancer treatment and found that BXXX could prolong the overall survival of liver cancer patients without obvious adverse reactions. So far, studies on the therapeutic potential of BXXX in GC have been insufficient as there is only one medical paper available on the literature database that is related to such subject.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wang et al conducted a clinical trial to evaluate the efficacy and safety of BXXX as monotherapy for patients with advanced HCC. 20 In the study, BXXX monotherapy exhibited the median progression-free survival (PFS) of 6.07 months, whereas sorafenib, the first-line treatment of advanced HCC, displayed the median PFS of 2.8 months in China. These findings suggested that the efficacy of BXXX may be superior to that of sorafenib in patients with advanced HCC, although this was not a direct comparison.…”
Section: Clinical Evaluation Of the Efficacy Of Tcmsmentioning
confidence: 99%
“…The results are promising since no drug-related serious adverse events were observed during the study and can be useful for treating patients with advanced HCC in a practical therapeutic environment. [78] 18. Application of BXD in treatment of adverse reactions of anticancer drugs For extensive-stage small cell lung carcinoma (SCLC), CPT-11 can be utilized as a first-line therapeutic medication in both first-line and second-line therapy.…”
Section: Application Of Bxd As a Complementary In Treatment Of Malign...mentioning
confidence: 99%
“…The results are promising since no drug-related serious adverse events were observed during the study and can be useful for treating patients with advanced HCC in a practical therapeutic environment. [ 78 ]…”
Section: Application Of Bxd As a Complementary In Treatment Of Malign...mentioning
confidence: 99%